PRESTASI BELAJAR FIQH DITINJAU DARI MINAT DAN GAYA BELAJAR PADA SISWA MADRASAH DINIYYAH NURUL UMMAH PUTRI TAHUN 2016/2017 - Eva Latipah; Khusnul Khotimah (Jurnal Pendidikan Agama Islam, 2017)
Subject of fiqh is one of compulsory subjects at level of Madrasah Ibtidaiyyah (MI) education. Therefore, having a high learning achievement in the course of fiqh is very important. This study aims to examine correlation between interest and learning styles with fiqh learning achievement. Population in this research is all student of Madrasah Diniyyah Nurul Ummah academic year 2016/2017 which amounted to 399 student. Sampling is done by purposive random sampling technique so that the sample is 60 students. Data were collected by using learning interest scale, learning style scale, and fiqh learning achievement document. Analysis technique used is regression analysis (anareg). Results showed: 1) there is a positive (r = 0.902) and significant (p = 0.001) correlation between learning interest with fikih achievement on students of Madrasah Diniyyah Nurul Ummah academic year 2016/2017; 2) there is no correlation between learning style with fikih learning achievement (r = 0,088 and p = 0,251); 3) there is a positive and significant correlation between learning style and learning interest with fikih learning achievement on Madrasah Diniyyah Nurul Ummah student of academic year 2016/2017 (F = 126,098 and p = 0,000).